1995
DOI: 10.1002/ana.410370320
|View full text |Cite
|
Sign up to set email alerts
|

Hyperkalemic periodic paralysis with cardiac dysrhythmia: A novel sodium channel mutation?

Abstract: A patient is presented with hyperkalemic periodic paralysis (HyperPP) and a cardiac dysrhythmia. An amino acid substitution (Val783Ile) in the adult skeletal muscle sodium channel gene was detected. Although lack of available family members precluded rigorous genetic tests, the sodium channel change may be responsible for HyperPP in this patient and could also be responsible for the associated cardiac dysrhythmia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…À Met1592Val occurred in all the patients in family 1, did not occurred in their relatives with no symptom. Chinnery et al reported a normoKPP case occurred the same mutation, which means Met1592Val does exist in different races and leads to normoKPP or hyperKPP (Chinnery et al 2002).`Val 781 Ile occurred in the patient and her father (with no symptom) in family 4, which had been reported to occur in a scattered hyperKPP case, and later functional expression study by Green et al showed probably a benign polymorphism (Baquero et al 1995;Green et al 1997).…”
Section: Discussionmentioning
confidence: 93%
“…À Met1592Val occurred in all the patients in family 1, did not occurred in their relatives with no symptom. Chinnery et al reported a normoKPP case occurred the same mutation, which means Met1592Val does exist in different races and leads to normoKPP or hyperKPP (Chinnery et al 2002).`Val 781 Ile occurred in the patient and her father (with no symptom) in family 4, which had been reported to occur in a scattered hyperKPP case, and later functional expression study by Green et al showed probably a benign polymorphism (Baquero et al 1995;Green et al 1997).…”
Section: Discussionmentioning
confidence: 93%
“…Genetic heterogeneity in periodic paralysis with cardiac arrhythmia is likely. Before our 1994 report, other patients with periodic paralysis and cardiac arrhythmias had been described (see Table I) [I, [4][5][6][7][8][9][10][11][12]. Only 2…”
Section: Discussionmentioning
confidence: 99%
“…However, with the recent description of a case of periodic paralysis with cardiac arrhythmias associated with a sodium channel mutation [12], it appears possible that there exist syndromes of periodic paralysis with cardiac involvement distinct from AS, although the gene defect has still to be identified. …”
Section: Discussionmentioning
confidence: 99%
“…This variant, currently classified as having no functional effect (Hofman classification; Table 2), was previously reported in association with hyperkalemic and normokalemic periodic paralysis. 33,34 However, a functional expression study supported the hypothesis that this variant should be classified as a rare benign polymorphism rather than a causative mutation. 35 No other family members were included in that study to evaluate segregation.…”
Section: Screening For Bs In Patients With Muscular Sodium Channelopamentioning
confidence: 93%